Evaluasi Lanskap Kebun Raya Batam Berdasarkan Preferensi dan Persepsi Masyarakat Kota Batam - Fathurrohman Fathurrohman; Afra Donatha Nimia Makalew; Akhmad Arifin Hadi (Diponegoro University, 2020)
The Batam Botanic Gardens (Kerabat) is a form of green open space in Batam City aimed at plant conservation activities, research, education, tourism and environmental services. The development of Kerabat until the end of 2018 has only reached around 35% and in 2019 the physical construction has been suspended. Before continuing the development so that the results are in line with expectations that serve as a place for plant conservation, research, community education, and tourism are needed to evaluate the Kerabat landscape. This study aimed to evaluate the Kerabat landscape that had been built based on the preferences and perceptions of the people in Batam City by comparing photos of Kerabat with other botanical garden photos. The results showed the Kerabat landscape based on the preferences and perceptions of the people in Batam City still did not show the character of the botanical garden landscape. Based on the analysis of the landscape preferences of the botanical garden from the photos chosen, the botanical garden character must have a landscape character that is beauty, green, beautiful, shady, organized, neat, comfortable for visitors and has good supporting facilities. Respondents preferences regarding the function of Kerabat are more for the conservation of plants and tourist attractions.